P310 Research priorities in digital technology for adolescents and young persons with inflammatory bowel disease. (19th June 2022) - Wong, Charlotte; Howsley, Philippa; Rao, Arati; Gasparetto, Marco; Kammermeier, Jochen; McLaughlin, John; Sebastian, Shaji; Smith, Philip J; Narula, Priya; Arebi, Naila
Abstract : Introduction: Evolution of digital technologies (DT) offers significant opportunities to transform inflammatory bowel disease (IBD) care. A James Lind Alliance (JLA) Priority Setting Partnership (PSP) aims to identify research priorities for DT in IBD. A survey was designed to identify unanswered questions or evidence uncertainties in the use of DT for adolescents and young persons with IBD. Methods: PSP meetings were held with key stakeholders within a Steering Group (SG) consisting of: paediatric and adult gastroenterologists with an interest in adolescent and young person care from BSPGHAN and BSG respectively; IBD specialist nurses; representatives from Crohn's in Childhood Research Association (CICRA) and Crohn's and Colitis UK (CCUK) charities; patient and parent representatives. The survey was designed through an iterative process, considered complete when there was saturation of changes and approved by all stakeholders. A pilot survey with a feedback questionnaire resulted in additional minor changes to the structure and content and provided examples of research priorities to guide participants. Results: A final survey consisting of three sections was approved by the SG. The first captures the respondent's role and connection with IBD. The second invites them to submit questions about DT in two areas: DT to support their condition and improve IBD care, and DT to improve communication with the healthcare team. Open-ended questions are used to allow elaboration of answers with examples generated from the pilot survey to assist respondents articulate research questions. An optional last section captures demographic information not linked to responses in previous sections. Conclusions: A survey ( Figure 1 ) was developed and piloted as a first step to identify unanswered questions. Research priorities will be identified using the JLA methodology to galvanise DT research that may translate into improved disease outcomes and quality of life.